Thermal, hydric, and physiological effects on watermelon due to wetted area variation - Allan Cunha Barros; Ricardo Barros Silva; Antônio Lucrécio dos Santos Neto; Lucas Melo Vellame; Maria Deyse Silva dos Santos; Antenor de Oliveira Aguiar Netto (Revista Ceres, 2024)
ABSTRACT The objective of this research was to evaluate leaf temperature, and watermelon yield components under wetted area percentages (PW) in irrigation located in the Agreste region of Northeastern Brazil. Two experiments were carried out in 2018 and 2019. The adopted statistical design was randomized blocks, with six replications and four treatments, in 2018: P1 = 13%, P2 = 14%, P3 = 19%, and P4 = 22%, in 2019: P5 = 12%, P6 = 15%, P7 = 16%, and P8 = 21% of PW. The meteorological variables analyzed were: air temperature (Ta) and rain. The experimental evaluations consisted of measuring the temperature of the plant’s vegetative canopy, tensiometry, mass, and BRIX. Air temperature was not a limiting factor for watermelon growth and development. The average was 195.88 mm, and the average leaf temperature of watermelon is 29.5 °C, a value lower than Ta. There was no statistically significant difference for fruit mass and BRIX, where the overall mean was 10.82 and 10.46 kg, respectively. Therefore, it is feasible to irrigate watermelon with wetted area percentages ranging from 12 to 22%, in localized irrigation systems, without generating physiological damage and reducing agricultural productivity and fruit quality.